Allocation and industry productivity: Accounting for firm turnover - Mika Maliranta; Niku Määttänen (The Research Institute of the Finnish Economy (ETLA), 2013)
Recent macroeconomic literature has stressed the importance of resource allocation between firms for aggregate productivity. An important issue, therefore, is how to measure allocative efficiency. We compare popular indicators of allocative efficiency, paying special attention to firm turnover. We first show how entering and exiting firms contribute to aggregate productivity and to the Olley-Pakes (OP) covariance component, which is currently the most popular measure of allocative efficiency. Our data cover essentially all firms and plants in the Finnish business sector. We then build a model of firm dynamics with endogenous turnover that is consistent with the main patterns of our empirical results and use it to test how well alternative indicators capture different allocation distortions. Our results demonstrate how and why commonly used indicators fail to capture certain distortions because of endogenous changes in firm turnover.
Keywords: E23; L16; O47; 330; productivity; firm dynamics; reallocation